Przedsiębiorstwo handlu zagranicznego w reformowanej gospodarce - Schroeder, Jerzy (Wydział Prawa i Administracji UAM, 1986)
The article attempts at defining a position and a role of a foreign trade enterprise in the conditions of implementation of the economic reform. The analysis of the previous practical solutions and theoretical assumptions leads to advancing a thesis that both the position and the role of these enterprises in the Polish economy are decided by the following factors: means of realization the Stahte monopoly of a foreign trade, and the related salutions in the sphere of organizing the foreign trade machinery, the existing system of managing the State economy and targets ow the foreign trade in the State economy. The author analyses and evaluates those factors and their influence on the conception of position and role of those enterprises in the economic system adopted on a. given stage of the State's economic development. A problem of position and role of those enterprises to be played in the future after implementation of the reform is also analysed.
A foreign trade enterprise in the reformed economy